Advancing Long-Term Outdoor Air Pollution Exposure Assessment for Health Studies: Lessons from a Multinational Research Initiative - Hanna Boogaard; Dan L. Crouse; Allison P. Patton; Ellen Mantus; Susanne Breitner-Busch; Jaime E. Hart; Anna Oudin; Shu Yang; Jeffrey D. Yanosky; John Volckens; Jana B. Milford (Current Environmental Health Reports, 2026)

NLRP3 inflammasome activation by particles and fibers: implications for human hazard assessment - Mathias Busch; Gerrit Bredeck; Hans Bouwmeester; Roel P. F. Schins (Archives of Toxicology, 2026)
The NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome has been shown to be involved in the manifestation of adverse effects following exposure to occupational, dietary and environmental particulate matter. In this review, we summarize knowledge on NLRP3 inflammasome activation by particles and fibers in vitro and in vivo, outline dominant activation mechanisms and discuss the link to human diseases. While the association between NLRP3 activation and development of diseases is well established for occupational exposure to mineral dusts like asbestos and quartz, the health effects of low-level exposure to environmental particulate pollutants, such as micro- and nanoplastics, desert dust or novel nanocomposites remain to be unraveled. Based on the combined literature of well-studied and emerging particles, we emphasize the relevance of testing for NLRP3 activation in the hazard assessment of novel particulate materials.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Tolerance to future elevated CO2 conditions in sablefish (Anoplopoma fimbria), a deep-water benthic dwelling fish species - Chase R. Williams; Evan P. Gallagher; Paul McElhany; D. Shallin Busch; Michael T. Maher; Andrew H. Dittman (Journal of Comparative Physiology A, 2026)

The electric vehicle transition: effects on copper supply dynamics in a net-zero future - S. Duex; P. Busch; A. Kendall (Resources, Conservation and Recycling, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Phenotypic and genotypic antimicrobial susceptibility of non-aureus staphylococci in dairy goats - Michelle P. Buckley; Fazal Sattar; Ganwu Li; Orhan Sahin; Roselle C. Busch; Amanda J. Kreuder; Paul J. Plummer; Patrick J. Gorden (Small Ruminant Research, 2025)

Oral inflammatory myofibroblastic tumour in a dog - S. Muller; M. Croci; I. Porcellato; P. Slootweg; M. Busch (Journal of Comparative Pathology, 2025)

Efficacy of two long-acting intramammary antimicrobials for curing subclinical mastitis due to non-aureus staphylococci in dairy goats - Michelle P. Buckley; Gustavo S. Silva; Roselle C. Busch; Orhan Sahin; Paul J. Plummer; Patrick J. Gorden (Small Ruminant Research, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Raising the bar: What determines the ambition level of corporate climate targets? - Clara Privato; Matthew P. Johnson; Timo Busch (Climatic Change, 2024)
Since the launch of the Science Based Targets initiative (SBTi), we have witnessed a steady increase in the number of companies committing to climate targets for large-scale reduction of greenhouse gas (GHG) emissions. While recent studies present various methodologies for establishing climate targets (e.g., sectoral decarbonization approach, near-term, long-term, net zero), we still don’t understand the explanatory factors determining the level of ambition companies demonstrate in target setting. In this paper, a two-stage qualitative study is conducted with a sample of 22 companies from five countries. First, these companies’ publicly disclosed climate targets are evaluated according to four target ambition criteria: target type, scope, timeframe, and temperature alignment. Secondly, multiple explanatory factors for target setting were identified during the content analysis of the interviews to see how present these factors appear in the ambition levels. Within companies with highly ambitious climate targets, the findings indicate that certain factors are highly present, including leadership engagement, continual management support, employee involvement, participation in climate initiatives, and stakeholder collaboration. Conversely, none of these key factors are highly present in companies with less ambitious climate targets. Rather, these companies strongly identify the initiating factors of market-related pressures and non-market stakeholder influence as being the driving forces behind their target setting. This paper contributes to the literature on corporate responses to climate change by expanding our understanding of explanatory factors for different corporate climate target ambition levels.

Low rate of detection of SARS-CoV-2 RNA in deceased tissue donors - Melissa A. Greenwald; Eduard Grebe; Valerie Green; Alyce Linthurst Jones; Jeffrey M. Linnen; Phillip Williamson; Michael P. Busch; Matthew J. Kuehnert (Cell and Tissue Banking, 2023)
Given the possibility for disease transmission, this study was performed to determine whether there is detectable SARS-CoV-2 viral RNA in the blood of deceased tissue donors. A retrospective analysis of blood samples from eligible deceased tissue donors from Oct 2019 through June 2020 was performed. Plasma aliquots were initially tested with a SARS-CoV-2 NAT Assay; positive samples were further tested using an alternate NAT and an antibody assay. The proportion of donors with confirmed RNAemia and 95% confidence intervals were computed. Of donor samples collected in 2019, 894 yielded valid results, with 6 initially positive, none of which confirmed positive by alternate NAT. Of donor samples collected in 2020, 2562 yielded valid initial NAT results, with 21 (0.8%) initially positive. Among those, 3 were confirmed by alternate NAT, 17 were not confirmed, and 1 had an invalid alternate NAT result. The rate of SARS-CoV-2 RNAemia in deceased tissue donors is approximately 1 per 1000, and it is unknown whether this RNAemia reflects the presence of infectious virus. Given these results, the risk of transmission through tissue is thought likely to be low.

Urinary concentration of phthalates and bisphenol A during minipuberty is associated with reproductive hormone concentrations in infant boys - Matilde Lærkeholm Müller; Alexander Siegfried Busch; Marie Lindhardt Ljubicic; Emmie N. Upners; Margit B. Fischer; Casper P. Hagen; Jakob Albrethsen; Hanne Frederiksen; Anders Juul; Anna-Maria Andersson (International Journal of Hygiene and Environmental Health, 2023)

Evaluating environmental controls on the exoskeleton density of larval Dungeness crab via micro computed tomography - Casey P. Saenger; Paul McElhany; Emily L. Norton; D. Shallin Busch; Samantha A. Siedlecki; Simone R. Alin; Richard A. Feely; Albert J. Hermann; Nina Bednaršek (Frontiers in Marine Science, 2023)
Dungeness crab ( Metacarcinus magister ) have significant socioeconomic value, but are threatened by ocean acidification (OA) and other environmental stressors that are driven by climate change. Despite evidence that adult harvests are sensitive to the abundance of larval populations, relatively little is known about how Dungeness megalopae will respond to these stressors. Here we evaluate the ability to use micro-computed tomography (μCT) to detect variations in megalope exoskeleton density and how these measurements reflect environmental variables and calcification mechanisms. We use a combination of field data, culture experiments, and model simulations to suggest resolvable differences in density are best explained by minimum pH at the time zoeae molt into megalopae. We suggest that this occurs because more energy must be expended on active ion pumping to reach a given degree of calcite supersaturation at lower pH. Energy availability may also be reduced due to its diversion to other coping mechanisms. Alternate models based on minimum temperature at the time of the zoea-megalope molt are nearly as strong and complicate the ability to conclusively disentangle pH and temperature influences. Despite this, our results suggest that carryover effects between life stages and short-lived extreme events may be particularly important controls on exoskeleton integrity. μCT-based estimates of exoskeleton density are a promising tool for evaluating the health of Dungeness crab populations that will likely provide more nuanced information than presence-absence observations, but future in situ field sampling and culture experiments are needed to refine and validate our results.

Interlaboratory comparison of an intestinal triple culture to confirm transferability and reproducibility - Angela A. M. Kämpfer; Ume-Kulsoom Shah; Shui L. Chu; Mathias Busch; Veronika Büttner; Ruiwen He; Barbara Rothen-Rutishauser; Roel P. F. Schins; Gareth J. Jenkins (In vitro models, 2022)
The development and improvement of advanced intestinal in vitro models has received increasing attention in recent years. While the availability of relevant in vitro models is pivotal to advance the replacement and reduction of animal use in research, their robustness is a crucial determinant for intra- and interlaboratory reproducibility. We have developed a standard protocol to build a triple culture model combining two types of human intestinal epithelial cells (Caco-2, HT29-MTX-E12) and macrophages (THP-1), which was tested for transferability and reproducibility between three laboratories. The epithelial tissue barrier development and triple culture stability were investigated as well as the models’ responses to the non-steroidal anti-inflammatory drug diclofenac in terms of barrier integrity, cytotoxicity, and cytokine release. The results of two partner laboratories were compared to previously established benchmark results and quality criteria. For the epithelial co-cultures, the results were overall highly comparable between the laboratories. The addition of THP-1 cells resulted in increased variability and reduced reproducibility. While good correlation was achieved in several endpoints, others showed substantial response differences between the laboratories. Some variations may be addressed with training or demonstrations, whereas others might be related to fundamental differences in the cell lines introduced during routine cell culture and maintenance. Our results underline the importance of interlaboratory transfer studies using standardised experimental procedures, including defined quality criteria and benchmarks, as well as of training when newly establishing complex in vitro models in laboratories.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Evaluation of Cardiotonic Steroid Modulation of Cellular Cholesterol and Phospholipid - Lilian N. D. Silva; Israel J. P. Garcia; Jessica M. M. Valadares; Marco Tulio C. Pessoa; Marina Marques Toledo; Matheus V. Machado; Mileane Souza Busch; Isabella Rocha; José Augusto F. P. Villar; Georgia C. Atella; Herica L. Santos; Vanessa F. Cortes; et al. (The Journal of Membrane Biology, 2021)

Reducing Data Deficiencies: Preliminary Elasmobranch Fisheries Surveys in India, Identify Range Extensions and Large Proportions of Female and Juvenile Landings - Shaili Johri; Isabella Livingston; Anjani Tiwari; Jitesh Solanki; Anissa Busch; Isabel Moreno; Sam R. Fellows; Michael P. Doane; Elizabeth A. Dinsdale (Frontiers in Marine Science, 2021)
Chondrichthyes, an ancient and diverse class of vertebrates, are crucial to the health of marine ecosystems. Excessive demand for chondrichthyan products has increased fishing pressure, threatening ∼30% of species with extinction in recent decades. India is the second-largest shark landing nation globally and the province of Gujarat, is the largest contributor to its shark exports. Despite their significant contribution to global fish supplies, chondrichthyan fisheries in Gujarat remain understudied and many species, data deficient, posing challenges to the conservation of remaining populations in the region. Here, we report results from taxonomic assessment of elasmobranchs at four key landing sites in Gujarat. We identified thirty-one species of sharks and rays with a significant bias toward capture of females and juveniles by fisheries. Our data indicate the presence of nursery areas for species such as Sphyrna lewini and Rhynchobatus laevis in the neritic areas off Gujarat. Further, we discovered extensions of the current distribution range for three species - Torpedo sinuspersici , Carcharhinus sorrah , and Rhinobatos punctifer . Taxonomic identities for a subset of species were confirmed using genomic analyses conducted with portable DNA sequencing tools. We present assessments for six data deficient species in the region – Rhinobatos annandalei , Rhinoptera jayakari , Maculabatis bineeshi, Pateobatis bleekeri, T. sinuspersici , and Carcharhinus amboinensis. Our investigation underscores species with urgent conservation needs and reduces data deficiencies. These data will inform and pivot future scientific and conservation efforts to protect remaining populations of some of the most vulnerable Chondrichthyes in the Arabian Seas Region.

Marine Citizen Science: Current State in Europe and New Technological Developments - Carlos Garcia-Soto; Jan J. C. Seys; Oliver Zielinski; J. A. Busch; S. I. Luna; Jose Carlos Baez; C. Domegan; K. Dubsky; I. Kotynska-Zielinska; P. Loubat; Francesca Malfatti; G. Mannaerts; et al. (Frontiers in Marine Science, 2021)
Marine citizen science is emerging with promising opportunities for science, policy and public but there is still no comprehensive overview of the current state in Europe. Based on 127 projects identified for the North Sea area we estimate there might be as much as 500 marine and coastal citizen science projects running in Europe, i.e., one marine citizen science project per ∼85 km of coastline, with an exponential growth since 1990. Beach-based projects are more accessible and hence most popular (60% of the projects), and the mean duration of the projects is 18–20 years. Current trends, topics, organizers, aims, and types of programme in terms of participation are presented in this overview. Progress in marine citizen science is specially enabled and promoted through technological developments. Recent technological advances and best practise examples are provided here, untapping the potential of smart mobile apps, do-it-yourself (DIY) technologies, drones, and artificial intelligence (AI) web services.

Elevated CO 2 impairs olfactory‐mediated neural and behavioral responses and gene expression in ocean‐phase coho salmon ( Oncorhynchus kisutch ) - Chase R. Williams; Andrew H. Dittman; Paul McElhany; D. Shallin Busch; Michael T. Maher; Theo K. Bammler; James W. MacDonald; Evan P. Gallagher (Global Change Biology, 2019)
Elevated concentrations of CO 2 in seawater can disrupt numerous sensory systems in marine fish. This is of particular concern for Pacific salmon because they rely on olfaction during all aspects of their life including during their homing migrations from the ocean back to their natal streams. We investigated the effects of elevated seawater CO 2 on coho salmon ( Oncorhynchus kisutch ) olfactory‐mediated behavior, neural signaling, and gene expression within the peripheral and central olfactory system. Ocean‐phase coho salmon were exposed to three levels of CO 2 , ranging from those currently found in ambient marine water to projected future levels. Juvenile coho salmon exposed to elevated CO 2 levels for 2 weeks no longer avoided a skin extract odor that elicited avoidance responses in coho salmon maintained in ambient CO 2 seawater. Exposure to these elevated CO 2 levels did not alter odor signaling in the olfactory epithelium, but did induce significant changes in signaling within the olfactory bulb. RNA‐Seq analysis of olfactory tissues revealed extensive disruption in expression of genes involved in neuronal signaling within the olfactory bulb of salmon exposed to elevated CO 2 , with lesser impacts on gene expression in the olfactory rosettes. The disruption in olfactory bulb gene pathways included genes associated with GABA signaling and maintenance of ion balance within bulbar neurons. Our results indicate that ocean‐phase coho salmon exposed to elevated CO 2 can experience significant behavioral impairments likely driven by alteration in higher‐order neural signal processing within the olfactory bulb. Our study demonstrates that anadromous fish such as salmon may share a sensitivity to rising CO 2 levels with obligate marine species suggesting a more wide‐scale ecological impact of ocean acidification.

The association of children’s mathematic abilities with both adults’ cognitive abilities and intrinsic fronto-parietal networks is altered in preterm-born individuals - J. G. Bäuml; C. Meng; M. Daamen; N. Baumann; B. Busch; P. Bartmann; D. Wolke; H. Boecker; A. Wohlschläger; C. Sorg; Julia Jaekel (Brain Structure and Function, 2017)

Extensive and interrelated subcortical white and gray matter alterations in preterm-born adults - C. Meng; J. G. Bäuml; M. Daamen; J. Jaekel; J. Neitzel; L. Scheef; B. Busch; N. Baumann; H. Boecker; C. Zimmer; P. Bartmann; D. Wolke; et al. (Brain Structure and Function, 2016)

Implications of p75NTR for dentate gyrus morphology and hippocampus-related behavior revisited - M. Dokter; R. Busch; R. Poser; M. A. Vogt; V. von Bohlen und Halbach; P. Gass; K. Unsicker; O. von Bohlen und Halbach (Brain Structure and Function, 2015)

Method Transfer, Partial Validation, and Cross Validation: Recommendations for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - R. J. Briggs; R. Nicholson; F. Vazvaei; J. Busch; M. Mabuchi; K. S. Mahesh; M. Brudny-Kloeppel; N. Weng; P. A. R. Galvinas; P. Duchene; Pei Hu; R. W. Abbott (The AAPS Journal, 2014)

Estimating Effects of Tidal Power Projects and Climate Change on Threatened and Endangered Marine Species and Their Food Web - D. SHALLIN BUSCH; CORREIGH M. GREENE; THOMAS P. GOOD (Conservation Biology, 2013)
Marine hydrokinetic power projects will operate as marine environments change in response to increased atmospheric carbon dioxide concentrations. We considered how tidal power development and stressors resulting from climate change may affect Puget Sound species listed under the U.S. Endangered Species Act (ESA) and their food web. We used risk tables to assess the singular and combined effects of tidal power development and climate change. Tidal power development and climate change posed risks to ESA‐listed species, and risk increased with incorporation of the effects of these stressors on predators and prey of ESA‐listed species. In contrast, results of a model of strikes on ESA‐listed species from turbine blades suggested that few ESA‐listed species are likely to be killed by a commercial‐scale tidal turbine array. We applied scenarios to a food web model of Puget Sound to explore the effects of tidal power and climate change on ESA‐listed species using more quantitative analytical techniques. To simulate development of tidal power, we applied results of the blade strike model. To simulate environmental changes over the next 50 years, we applied scenarios of change in primary production, plankton community structure, dissolved oxygen, ocean acidification, and freshwater flooding events. No effects of tidal power development on ESA‐listed species were detected from the food web model output, but the effects of climate change on them and other members of the food web were large. Our analyses exemplify how natural resource managers might assess environmental effects of marine technologies in ways that explicitly incorporate climate change and consider multiple ESA‐listed species in the context of their ecological community. Estimación de los Efectos de Proyectos de Energía de las Mareas y el Cambio Climático sobre Especies Marinas Amenazadas y en Peligro y su Red Alimentaria

Depot naltrexone decreases rewarding properties of sugar in patients with opioid dependence - Daniel D. Langleben; Elliot L. Busch; Charles P. O’Brien; Igor Elman (Psychopharmacology, 2012)

Narrow species concepts in the Frullania dilatata–appalachiana–eboracensis complex (Porellales, Jungermanniopsida): evidence from nuclear and chloroplast DNA markers - A. Bombosch; A. Wieneke; A. Busch; R. Jonas; J. Hentschel; H.-P. Kreier; B. Shaw; A. J. Shaw; J. Heinrichs (Plant Systematics and Evolution, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Disruption of the Gardos channel (KCa3.1) in mice causes subtle erythrocyte macrocytosis and progressive splenomegaly - Ivica Grgic; Brajesh P. Kaistha; Steffen Paschen; Anuradha Kaistha; Christoph Busch; Han Si; Kernt Köhler; Hans-Peter Elsässer; Joachim Hoyer; Ralf Köhler (Pflügers Archiv - European Journal of Physiology, 2009)

Development of polymorphic tetranucleotide microsatellites for pinyon jays (Gymnorhinus cyanocephalus) - Joseph D. Busch; Russell Benford; Talima Pearson; Eldon Palmer; Russell P. Balda; Paul Keim (Conservation Genetics, 2009)

Laboratory Experiments on Environmental Friendly Means to Improve Coalbed Methane Production by Carbon Dioxide/Flue Gas Injection - S. Mazumder; K. H. A. A. Wolf; P. van Hemert; A. Busch (Transport in Porous Media, 2008)

Genetic structure in a solitary rodent ( Ctenomys talarum ): implications for kinship and dispersal - A. P. CUTRERA; E. A. LACEY; C. BUSCH (Molecular Ecology, 2005)
The genetic structure of a population provides critical insights into patterns of kinship and dispersal. Although genetic evidence of kin structure has been obtained for multiple species of social vertebrates, this aspect of population biology has received considerably less attention among solitary taxa in which spatial and social relationships are unlikely to be influenced by kin selection. Nevertheless, significant kin structure may occur in solitary species, particularly if ecological or life history traits limit individual vagility. To explore relationships between genetic structure, kinship, and dispersal in a solitary vertebrate, we compared patterns of genetic variation in two demographically distinct populations of the talar tuco‐tuco ( Ctenomys talarum ), a solitary species of subterranean rodent from Buenos Aires Province, Argentina. Based on previous field studies of C. talarum at Mar de Cobo (MC) and Necochea (NC), we predicted that natal dispersal in these populations is male biased, with dispersal distances for males and females being greater at NC. Analyses of 12 microsatellite loci revealed that in both populations, kin structure was more apparent among females than among males. Between populations, kinship and genetic substructure were more pronounced at MC. Thus, our findings were consistent with predicted patterns of dispersal for these animals. Collectively, these results indicate that populations of this solitary species are characterized by significant kin structure, suggesting that, even in the absence of sociality and kin selection, the spatial distributions and movements of individuals may significantly impact patterns of genetic diversity among conspecifics.

Evidence for Selection of more Adapted Human Immunodeficiency Virus Type 1 Recombinant Strains in a Dually Infected Transfusion Recipient - Luciana Jesus Costa; Allen J. Mayer; Michael P. Busch; Ricardo Sobhie Diaz (Virus Genes, 2004)

Characterisation of oxidised 7Fe dicluster ferredoxins with NMR spectroscopy - Jonathan P. Hannan; Johanneke L. H. Busch; Jacques Breton; Richard James; Andrew J. Thomson; Geoffrey R. Moore; S. L. Davy (JBIC Journal of Biological Inorganic Chemistry, 2000)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Depression After Mild Traumatic Brain Injury: A Review of Current Research - Chardelle R. Busch; Herbert P. Alpern (Neuropsychology Review, 1998)

Lack of interaction between meloxicam and warfarin in healthy volunteers - D. Türck; C. A. P. F. Su; G. Heinzel; U. Busch; E. Bluhmki; J. Hoffmann (European Journal of Clinical Pharmacology, 1997)